Adverse Life Experience and Psychological Distress in Adolescence: Moderating and Mediating Effects of Emotion Regulation and Rumination - Boyes, Mark; Hasking, Penelope; Martin, G. (John Wiley & Sons Ltd., 2016)
The current study tested whether emotion regulation and rumination moderated and/or mediated the relationship between accumulated adverse life experience and psychological distress in adolescence. In class, Australian high school students (n = 2637, 12–18 years, 68% female) from 41 schools completed well-validated measures of adverse life experience, emotion regulation, rumination and psychological distress, and were followed up 1 year later (n = 1973, 75% retention rate). Adjusting for age, gender and baseline psychological distress, adverse life experience predicted psychological distress 1 year later. Expressive suppression and rumination were positively associated with psychological distress. Cognitive reappraisal was negatively associated with psychological distress and moderated the relationship between adverse life experience and psychological distress. This relationship was also partially mediated by cognitive reappraisal, expressive suppression and rumination. Promoting cognitive reappraisal and minimizing expressive suppression and rumination may be useful strategies to improve mental health for adolescents who have experienced adverse life events. Future research should examine whether adolescents who have experienced adverse life events can be trained in effective emotion regulation strategies and whether this training can prevent development of psychological maladjustment.